Evidence for a relative excess of lysyl hydroxylase in chick embryo tendon and cartilage compared with bone and skin - Puistola, Ulla; Anttinen, Henrik (Biochimica et biophysica acta, 1982)
Various chick embryo tissues were incubated in vitro with a range of Zn 2+ concentrations, and inhibition of the hydroxylations of collagen proline and lysine residues was studied in the intact tissues. At an constant inhibition level of proline hydroxylation, lysine hydroxylation proved to be inhibited more in the skin and bone than in the tendon and cartilage. The ratios of lysyl hydroxylase to prolyl hydroxylase activity were also distinctly lower in the former than in the latter. The variations observed in the reduction of lysine hydroxylation by Zn 2+ thus correlate well with the differences seen in the enzyme activity ratios. No differences are found in the K i values for Zn 2+ between purified prolyl and lysyl hydroxylases or between the same enzymes from different tissues, and consequently the differences in lysine hydroxylation inhibition between the various tissues cannot be explained by differences in the kinetic constants. Recent studies also suggest that the existence of tissue-specific lysyl hydroxylase isoenzymes is improbable. The data thus suggest that there is a relative excess of lysyl hydroxylase activity in tissues such as tendon and cartilage, in which the lysine hydroxylation was less sensitive to Zn 2+ inhibition, compared with skin and bone, where lysine hydroxylation was inhibited to a greater extent. These data are in a good agreement with the findings concerning variation in the reduction in lysine hydroxylation in different tissues with age or in the Ehlers-Danlos Syndrome Type VI.